2016
DOI: 10.2139/ssrn.2773874
|View full text |Cite
|
Sign up to set email alerts
|

The Time-Varying Risk of Macroeconomic Disasters

Abstract: While time-varying disasters can explain many characteristics of financial markets, their quantitative assessment is still missing. We propose a latent variable approach to estimate the time-varying probability of a macroeconomic disaster, using a dataset of 42 countries over more than 100 years. We find that disaster risk is volatile and persistent, strongly correlates with the dividend yield, and forecasts stock returns. A state-of-the-art model calibrated with our disaster risk estimates generates a large a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 154 publications
(101 reference statements)
1
7
0
Order By: Relevance
“…However, these results confirm the superiority of QNN and DNDT, which improve precision results compared to other previous studies on estimating Asset Pricing models (Chen et al, 2017; Gu et al, 2020, 2021; Marfè & Penasse, 2016). For example, Marfè and Penasse (2016) obtained an 86% ROC curve to exclusively predict disaster risk in the price of shares. Chen et al (2017) obtained a mean goodness of fit in their different estimated parameters of 30% using the OLS technique for their estimation.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…However, these results confirm the superiority of QNN and DNDT, which improve precision results compared to other previous studies on estimating Asset Pricing models (Chen et al, 2017; Gu et al, 2020, 2021; Marfè & Penasse, 2016). For example, Marfè and Penasse (2016) obtained an 86% ROC curve to exclusively predict disaster risk in the price of shares. Chen et al (2017) obtained a mean goodness of fit in their different estimated parameters of 30% using the OLS technique for their estimation.…”
Section: Resultssupporting
confidence: 85%
“…The specification used for the volatility, consumption, and dividend parameters are equivalent to those applied in previous works (Chen et al, 2017; Marfè & Penasse, 2016; Schorfheide et al, 2018). Typically, volatility is found as a variable with a positive sign (Gu et al, 2021).…”
Section: Macro Asset Pricing Model and Neural Network Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoré and Szczerbowicz (2017) further showed how to extend this approach to a New Keynesian environment, and found that disaster risk shocksn-again, absent of actual disaster realization-, generate procyclical responses of consumption, investment, labor, wage, and inflation, simultaneously to the recession and rise in equity premium. Further empirical evidence by Siriwardane (2015) and Marfè and Penasse (2017) support the relationship between changes in the probability of a disaster and macroeconomic variables.…”
Section: Introductionmentioning
confidence: 83%
“…More speci…cally we refer to Gabaix (2012), Gourio (2012), andWachter (2013), who demonstrate that this variability can explain many asset-pricing puzzles. In addition, Marfe and Penasse (2017) …nd empirical evidence for disaster-risk variablity. Another body of literature assumes imperfect information about rare disaster risk and argues that parameter learning implies more pessimistic disaster-risk beliefs after a rare disaster (Collin-Dufresne et al, 2016, Koulovatianos and Wieland, 2017, and Kozlowski et al, 2017.…”
Section: Introductionmentioning
confidence: 99%